Investigating the genetic basis of cisplatin-induced ototoxicity in adult South African patients - Spracklen, Timothy Francis (Division of Human Genetics, 2016)
Cisplatin, a potent chemotherapeutic agent, is widely used in the treatment of numerous soft-tissue cancers. Although high cure rates can be achieved when cisplatin is incorporated in chemotherapy regimens, the therapeutic utility of the drug may be limited by the development of dose-limiting adverse reactions in patients. A prevalent reaction to cisplatin is ototoxicity, or drug-induced hearing loss, which occurs when the drug accumulates in and damages cells of the inner ear, leading to permanent and progressive hearing impairment. In this investigation, two approaches were employed to explore the role of genetics in cisplatin response amongst South African cancer patients (n = 214). Using a candidate gene approach, which investigated variants in six genes which are involved in drug transport and processing, potential modifiers in the genes nuclear factor, erythroid 2-like 2 (NFE2L2) and solute carrier family 22, member 2 (SLC22A2) were identified. SLC22A2 encodes a known transporter of cisplatin, and the variant rs316019 conferred potentially protective effects against Chang- and TUNE-graded ototoxicity through a reduced transport of the drug (p = 0.039 and p = 0.031, respectively). Similarly, the variant NFE2L2 rs6721961 was possibly protective, as it occurred more frequently in patients who did not develop hearing impairment according to four different ototoxicity grading scales during high-dose (≥ 200 mg/m2) cisplatin treatment (ASHA, p = 0.001; Chang, p = 0.022; CTCAE, p = 0.001; TUNE, p = 0.028). When supplementing the prospective cohort with retrospective patient data, an increased susceptibility of indigenous African patients to Chang grade > 0 ototoxicity was observed (p = 0.001). For this reason, whole-exome sequencing was conducted on a subset of the patient cohort (n = 11), focussing on individuals of African origin who represented the phenotype extremes. Potential genetic modifiers were identified in genes involved in various biological processes, including transmembrane transport, development, hearing, the response to DNA damage, immune reactions and signalling pathways, implicating many previously unreported genes in the cellular response to cisplatin as well as its ototoxicity. The results reported in this study indicate that genetic information can improve predictive models of cisplatin response, although there are many novel genes which should be explored in the South African population. Identifying these genetic modifiers, such as those in SLC22A2 and NFE2L2, has the potential to further our understanding of this adverse drug reaction, and may assist in the future personalisation of treatment plans in the management of cancer.